Collaborative Writing: an Effective Teaching Strategy to Teach Writing Paragraphs - Mukminatus Zuhriyah; Sayid Ma'rifatulloh; Maskhurin Fajarina; Ria Kamilah Agustina; Sakhi Herwiana (IKIP PGRI Pontianak, 2023)
The students’ writing ability was low because they were reluctant to cooperate with their friends when writing. Therefore, the researchers were interested in investigating the effectiveness of collaborative writing for teaching writing paragraphs in this post-pandemic. This study used a pre-experimental design, a one group pre-test post-test research design. Twenty-five students of an English department in a private university in East Java became the population as well as the sample. Pre-test and post-test of writing a paragraph were used to collect the data. The researchers used a descriptive statistics and a paired-sample test to analyze the data. The results show that the students’ writing average score increased from 68.6 to 81.2. Meanwhile, the result of a paired- sample test tells that sig. (2-tailed) was 0.000. It means that the implementation of collaborative writing was effective to teach writing paragraphs. Hopefully, the EFL teachers use collaborative writing in their writing classes.